A method for melting interstitial carbon element alloyed high-temperature titanium alloy ingot
By using layered fabric form and vacuum consumable arc melting three times during the smelting process of titanium alloy ingots, the problem of difficult to accurately control the element content of multi-main high-carbon titanium alloy ingots is solved, and the ingot with high metallurgical quality and composition uniformity is achieved, and the mechanical properties and service life of the alloy are improved.
Patent Information
- Application Number
- CN202411968930.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to accurately control the element content of multi-main high-carbon titanium alloy ingots, resulting in uneven element segregation and component distribution, affecting the mechanical properties and service life of the alloy.
The appropriate C addition method and smelting method are adopted to ensure that the raw materials are fully mixed through primary and secondary mixtures, press them in the form of layered fabrics, and vacuum self-consumable arc melting is carried out three times, controlling the corresponding parameters of the smelting process to achieve accurate control of element content and uniform distribution of components.
A multi-main high-temperature titanium alloy ingot with high metallurgy quality and good surface quality is achieved, ensuring the precise control of C element and the composition uniformity of the alloy, and improving the mechanical properties and service life of the alloy.
Smart Images

Figure CN119736507A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy materials and preparation thereof, and in particular relates to a method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot. Background Art
[0002] The key technology of interstitial element alloying is used to improve the thermal stability of high-temperature titanium alloys, which is of great theoretical and practical significance for improving the comprehensive mechanical properties and service reliability. Interstitial element carbon has a significant effect on the improvement of titanium alloy structure and mechanical properties. Carbon alloying of high-temperature titanium alloys can improve the heat treatment process window of α+β phase region, and the ordered α 2 The distribution of phases and silicides is more uniform, which helps to improve the service life of the alloy. High-temperature titanium alloys have the advantages of high specific strength, high temperature resistance, corrosion resistance, oxidation resistance, and good creep resistance, making them the key materials in the field of aerospace equipment. Among them, the high-temperature titanium alloy Ti-Al-Sn-Zr-Mo-Ta-Nb-Si (wt.%) is a near-α-type high-temperature titanium alloy independently developed by my country. This alloy adds three isomorphous high-melting-point β-type stabilizing elements Ta, Mo, and Nb to the Ti-Al-Sn-Zr-Si near-α system, which makes the alloy have higher high-temperature strength, high-temperature oxidation resistance and thermal stability. It is a new type of high-temperature titanium alloy urgently needed by my country's aviation and defense industries. Carbon is added to the high-temperature titanium alloy Ti-Al-Sn-Zr-Mo-Ta-Nb-Si (wt.%) to precipitate carbide particles with TiC structure to pin the grain boundaries and refine the β grains. In addition to the advantages of high operating temperature, low density and high strength, the high-temperature titanium alloy also has many properties such as good fracture toughness, creep resistance, fatigue resistance and thermal stability, and can serve stably for a long time in an environment of 600°C.
[0003] As the parent material of titanium alloy plate / foil structural parts, the quality of multi-principal high-temperature titanium alloy ingots after carbon addition will directly affect the processing and use performance of rods, plates and foils. The composition of Ti-Al-Sn-Zr-Mo-Ta-Nb-Si titanium alloy itself is extremely complex, containing many high melting point and easily segregated elements, and the density and melting point differences of each element are large. Among them, the melting points of Nb, Mo and Ta elements are relatively high, which are 2467℃, 2662℃ and 2996℃ respectively, and the density is 38.4g / cm 3 , 10.22g / cm 3 and 16.6 g / cm 3 The melting point of the low melting point element Sn is 232°C and the density is 7.31 g / cm 3 , in which interstitial C elements are added. The melting point of C element is as high as 3550℃, which is quite different from the melting point and density of titanium, further increasing the difficulty of preparing the high-carbon ingot.
[0004] In summary, it is necessary to provide a suitable C addition method and smelting method to achieve precise control of the content of each element in the interstitial carbon element alloyed titanium alloy ingot, ensure the uniformity of each element in the ingot and the density of the solidification structure, which will greatly ensure the mechanical properties of the interstitial carbon element alloyed high-temperature titanium alloy and provide greater guarantee for the development of high-temperature titanium alloy materials. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a smelting method for interstitial carbon element alloyed high-temperature titanium alloy ingots in view of the deficiencies of the above-mentioned prior art. The method selects suitable raw materials, performs appropriate raw material pretreatment, special material distribution method, and uses a vacuum consumable arc melting furnace for three smeltings to control the corresponding parameters of the smelting process. Effective measures are taken in all links of the whole process to solve the problem that the element content of multi-principal high-carbon titanium alloys in the existing smelting method is difficult to accurately control and the alloy element segregation, and prepares multi-principal high-temperature titanium alloy ingots with high metallurgical quality, good surface quality, and accurately controlled C content.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a smelting method of interstitial carbon element alloyed high-temperature titanium alloy ingot, characterized in that the method comprises the following steps:
[0007] Step 1: Mix titanium sponge particles with a particle size of 2 mm to 3 mm, flake graphite powder and titanium oxide powder, and then add intermediate alloy powder for secondary mixing to obtain a mixture;
[0008] Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in a pressing mold in a layered wrapped cloth form from bottom to top, and then press them, and repeat the above process to obtain multiple electrode blocks;
[0009] Step 3, welding the multiple electrode blocks obtained in step 2 to obtain a consumable electrode;
[0010] Step 4, melting the consumable electrode obtained in step 3 to obtain an ingot;
[0011] Step 5, performing secondary smelting on the primary ingot obtained in step 4 to obtain a secondary ingot;
[0012] Step 6: Smelt the secondary ingot obtained in step 5 three times to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05% to 0.20%.
[0013] The present invention uses flake graphite powder to introduce the C element, thereby ensuring the accuracy of the composition of the raw material corresponding to the C element, and avoiding the inadequacy of the C element control caused by the use of a C-containing master alloy, which makes it impossible to achieve accurate control of its composition.
[0014] The present invention mixes titanium sponge particles with a particle size of 2 mm to 3 mm, graphite flake powder and titanium oxide powder with the master alloy powder in two mixing steps, so that the powdered raw materials are fully adhered to the titanium sponge particles, thereby avoiding the reduction of the content of C and O elements due to material spillage during the pressing of the electrode block, and ensuring the precise control of the C and O element components;
[0015] The present invention combines the sequential solidification characteristics of each element in the smelting process and the value of the distribution coefficient K in the titanium alloy, and adopts a layered wrapped cloth form when pressing the electrode, that is, sponge titanium particles with a particle size of 0.83mm to 12.7mm are used to sandwich the mixture in the middle, so as to better cover and wrap the mixture, reduce the uneven distribution of components caused by burning or unmelting of elements with different melting points, avoid fractures caused by internal stress during the pressing process, and ensure the quality of the electrode block.
[0016] In the present invention, titanium sponge particles with a particle size of 2 mm to 3 mm, titanium sponge particles with a particle size of 0.83 mm to 12.7 mm and intermediate alloys are selected by a color sorter and a magnetic separator to remove foreign matter and defective materials, thereby ensuring the quality of the raw materials.
[0017] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the sponge titanium particles with a particle size of 2 mm to 3 mm in step 1 and the sponge titanium particles with a particle size of 0.83 mm to 12.7 mm in step 2 both meet the requirements of grade 0 sponge titanium or grade 0 in GB / T 2524-2019 standard. A The invention controls the standard of titanium sponge particles and the impurities in the titanium sponge particles, thereby ensuring the purity of the high-temperature titanium alloy ingot alloyed with interstitial carbon elements.
[0018] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the particle size of the flake graphite powder in step 1 is 20 mesh to 40 mesh, the mass purity is 3N grade, the particle size of the titanium oxide powder is 300 mesh to 400 mesh, and the particle size of the intermediate alloy powder is 1 mm to 6 mm. The present invention ensures the uniform distribution of C element and other elements during the smelting process by controlling the particle sizes of the flake graphite powder, titanium oxide powder and intermediate alloy powder.
[0019] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the master alloy in step 1 includes an aluminum-molybdenum alloy, a niobium-titanium-aluminum alloy, an aluminum-silicon alloy, a titanium-tin alloy and an aluminum-tantalum alloy. The present invention adjusts the composition of the interstitial carbon element alloyed high-temperature titanium alloy ingot by controlling the composition of the master alloy to prepare interstitial carbon element alloyed high-temperature titanium alloy ingots with different compositions.
[0020] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the time of the primary mixing and the secondary mixing in step 1 are not less than 3 minutes. The present invention ensures that the raw materials are fully mixed and uniform by controlling the time of the primary mixing and the secondary mixing, avoids the reduction of the content of C and O elements due to material spillage during the pressing of the electrode block, and ensures the precise control of the C and O element components.
[0021] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the layered wrapped cloth form described in step 2 is specifically that the part close to the pressing mold is covered and filled with sponge titanium with a particle size of 0.83mm to 12.7mm, and the middle is a mixture, and the mass of the upper and lower layers of 0.83mm to 12.7mm sponge titanium particles is equal. The present invention sandwiches the mixture in the middle with sponge titanium particles with a particle size of 0.83mm to 12.7mm, better covers and wraps the mixture, reduces the uneven distribution of components caused by burning or unmelting of various elements with different melting points, avoids fractures caused by internal stress during the pressing process, and ensures the quality of the electrode block.
[0022] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the group welding in step 3 is performed by using a vacuum plasma welding gun. The present invention ensures the quality of the consumable electrode by using a vacuum plasma welding gun for group welding.
[0023] The above-mentioned method for smelting interstitial carbon element alloyed high-temperature titanium alloy ingots is characterized in that the primary smelting in step four is vacuum consumable arc melting using a vacuum consumable arc furnace, the vacuum degree of the primary smelting is less than 0.8 Pa, the smelting current in the normal smelting stage is 17kA~20kA, the smelting voltage is 30V~35V, the arc stabilizing current is 20A, and the commutation time of the arc stabilizing current is 30s.
[0024] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the secondary smelting in step five is performed by vacuum consumable arc melting in a vacuum consumable arc furnace, the vacuum degree of the secondary smelting is less than 0.8 Pa, the smelting current in the normal smelting stage is 20kA~25kA, the smelting voltage is 35V~37V, the arc stabilization current is 18A, and the commutation time of the arc stabilization current is 30s.
[0025] The above-mentioned method for smelting an interstitial carbon element alloyed high-temperature titanium alloy ingot is characterized in that the three smeltings in step six are performed by vacuum consumable arc melting in a vacuum consumable arc furnace, the vacuum degree of the three smeltings is less than 0.8 Pa, the smelting current in the normal smelting stage is 25kA~30kA, the smelting voltage is 37V~42V, the arc stabilizing current is 16A, and the commutation time of the arc stabilizing current is 30s.
[0026] The present invention promotes diffusion and migration of solute element atoms in the solution, reduces and eliminates dendrite segregation, ensures uniformity of the composition of the entire ingot, realizes alloying of interstitial carbon elements, and avoids the deficiencies of various ingot composition unevenness, micro-area dendrite segregation, and metallurgical defects on the surface and inside of the ingot caused by the conventional double melting process of vacuum induction melting and vacuum consumable melting.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. The present invention mixes titanium sponge particles with a particle size of 2 mm to 3 mm, flake graphite powder, titanium oxide powder and master alloy powder, and then spreads them in a layered wrapped cloth form, and then smelts them, thereby ensuring the accuracy of the composition of the C element corresponding to the raw material, ensuring the precise control of the composition of the C and O elements, reducing the uneven distribution of components caused by burning or unmelting of various elements with different melting points, and obtaining a high-temperature titanium alloy ingot with a uniform carbon content of 0.05% to 0.20%.
[0029] 2. The present invention ensures that the raw materials are fully mixed evenly by controlling the time of the primary mixing and the secondary mixing, thereby avoiding the reduction of the content of C and O elements due to material spillage during the pressing process of the electrode block, and ensuring the precise control of the C and O element composition.
[0030] 3. The present invention sandwiches the mixture with sponge titanium particles with a particle size of 0.83mm to 12.7mm, so as to better cover and wrap the mixture, reduce the uneven distribution of components caused by burning or unmelting of elements with different melting points, avoid breakage caused by internal stress during the pressing process, and ensure the quality of the electrode block.
[0031] 4. The present invention promotes the diffusion and migration of solute element atoms in the solution, reduces and eliminates dendritic segregation, ensures the overall composition uniformity of the ingot, realizes interstitial carbon element alloying, and avoids the deficiencies of various ingot composition unevenness, micro-area dendritic segregation, and ingot surface and internal metallurgical defects caused by the conventional double melting process of vacuum induction melting and vacuum consumable melting by performing primary melting, secondary melting and tertiary melting and controlling the melting parameters.
[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a physical picture of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 1 of the present invention.
[0034] Figure 2 It is a schematic diagram of the sampling position of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 1 of the present invention.
[0035] Figure 3 It is an element distribution diagram of each sampling position of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 1 of the present invention.
[0036] Figure 4 This is a physical picture of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 2 of the present invention.
[0037] Figure 5 It is a schematic diagram of the sampling position of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 2 of the present invention.
[0038] Figure 6 It is an element distribution diagram of each sampling position of the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0039] Example 1
[0040] This embodiment is to prepare a high-temperature titanium alloy ingot alloyed with interstitial carbon elements having a composition of Ti-6Al-3.5Sn-3.5Zr-1.0Mo-1.2Ta-0.8Nb-0.5Si-0.08C.
[0041] This embodiment includes the following steps:
[0042] Step 1, titanium sponge particles with a particle size of 2mm to 3mm, 3N flake graphite powder with a particle size of 20 mesh to 40 mesh, and titanium oxide powder with a particle size of 300 mesh to 400 mesh are mixed for more than 3 minutes, and then aluminum-molybdenum alloy powder, niobium-titanium-aluminum alloy powder, aluminum-silicon alloy powder, titanium-tin alloy powder and aluminum-tantalum alloy powder with a particle size of 1mm to 6mm are added for secondary mixing for more than 3 minutes to obtain a mixture; the titanium sponge particles with a particle size of 2mm to 3mm meet the 0 grade titanium sponge or 0 in GB / T 2524-2019 standard A Requirements for grade titanium sponge;
[0043] Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in the pressing mold in a layered wrapped cloth form from bottom to top, and the mass of the titanium sponge particles of 0.83 mm to 12.7 mm in the upper and lower layers is equal, and then press, and repeat the above process to obtain a plurality of electrode blocks; the titanium sponge particles with a particle size of 0.83 mm to 12.7 mm meet the GB / T 2524-2019 standard 0 grade titanium sponge or 0 A Requirements for grade titanium sponge;
[0044] Step 3: welding the multiple electrode blocks obtained in step 2 by using a vacuum plasma welding gun to obtain a consumable electrode;
[0045] Step 4: The consumable electrode obtained in step 3 is melted once in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a melting current of 17kA-20kA in a normal melting stage, a melting voltage of 30V-35V, an arc stabilizing current of 20A, and a switching time of the arc stabilizing current of 30s to obtain an ingot;
[0046] Step 5, the primary ingot obtained in step 4 is subjected to secondary smelting in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a smelting current of 20kA-25kA in a normal smelting stage, a smelting voltage of 35V-37V, an arc stabilizing current of 18A, and a switching time of the arc stabilizing current of 30s to obtain a secondary ingot;
[0047] Step six, the secondary ingot obtained in step five is melted three times in a vacuum consumable arc furnace at a vacuum degree of less than 0.8Pa, a melting current of 25kA-30kA in the normal melting stage, a melting voltage of 37V-42V, an arc stabilizing current of 16A, and a switching time of the arc stabilizing current of 30s to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05%-0.20%.
[0048] Figure 1 is a physical picture of the interstitial carbon element alloyed high temperature titanium alloy ingot prepared in this embodiment, Figure 1 It can be seen that the prepared interstitial carbon element alloyed high-temperature titanium alloy ingot has a larger volume, no surface interlayer, obvious cold shut, scarring, smaller ingot head flash, and the ingot body is bright and free of oxidation.
[0049] The interstitial carbon element alloyed high temperature titanium alloy ingot prepared in this example was sampled at different positions. Figure 2 ,from Figure 2 It can be seen that samples are taken at various positions in the middle of the ingot body of the interstitial carbon element alloyed high-temperature titanium alloy ingot, and the sampling positions are numbered. Then the sampling results are tested for composition. The results are shown in Figure 3 ,from Figure 3 It can be seen that the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this embodiment has a uniform overall composition, no obvious composition fluctuation, and is consistent with the batching value.
[0050] The interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this example was sampled at the top, middle and bottom, and the composition was tested. The results are shown in Table 1.
[0051] Table 1
[0052] element Upper part (wt.%) Middle (wt.%) Lower part (wt.%) Al 5.95 5.99 5.98 Mo 0.99 0.98 1.00 Nb 0.80 0.79 0.81 Si 0.49 0.50 0.50 Sn 3.49 3.50 3.50 Ta 1.20 1.19 1.20 Zr 3.49 3.48 3.47 C 0.08 0.08 0.08
[0053] It can be seen from Table 1 that the composition differences of the interstitial carbon element alloyed high-temperature titanium alloy ingots prepared in this embodiment are all controlled within 0.1%.
[0054] Example 2
[0055] This embodiment is to prepare an interstitial carbon element alloyed high-temperature titanium alloy ingot with a composition of Ti-7Al-2.5Sn-2.5Zr-1.5Mo-2.0Ta-1.0Nb-1.0Si-0.20C.
[0056] This embodiment includes the following steps:
[0057] Step 1, titanium sponge particles with a particle size of 2mm to 3mm, 3N flake graphite powder with a particle size of 20 mesh to 40 mesh, and titanium oxide powder with a particle size of 300 mesh to 400 mesh are mixed for more than 3 minutes, and then aluminum-molybdenum alloy powder, niobium-titanium-aluminum alloy powder, aluminum-silicon alloy powder, titanium-tin alloy powder and aluminum-tantalum alloy powder with a particle size of 1mm to 6mm are added for secondary mixing for more than 3 minutes to obtain a mixture; the titanium sponge particles with a particle size of 2mm to 3mm meet the 0 grade titanium sponge or 0 in GB / T 2524-2019 standard A Requirements for grade titanium sponge;
[0058] Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in the pressing mold in a layered wrapped cloth form from bottom to top, and the mass of the titanium sponge particles of 0.83 mm to 12.7 mm in the upper and lower layers is equal, and then press, and repeat the above process to obtain a plurality of electrode blocks; the titanium sponge particles with a particle size of 0.83 mm to 12.7 mm meet the GB / T 2524-2019 standard 0 grade titanium sponge or 0 A Requirements for grade titanium sponge;
[0059] Step 3: welding the multiple electrode blocks obtained in step 2 by using a vacuum plasma welding gun to obtain a consumable electrode;
[0060] Step 4: The consumable electrode obtained in step 3 is melted once in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a melting current of 17kA-20kA in a normal melting stage, a melting voltage of 30V-35V, an arc stabilizing current of 20A, and a switching time of the arc stabilizing current of 30s to obtain an ingot;
[0061] Step 5, the primary ingot obtained in step 4 is subjected to secondary smelting in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a smelting current of 20kA-25kA in a normal smelting stage, a smelting voltage of 35V-37V, an arc stabilizing current of 18A, and a switching time of the arc stabilizing current of 30s to obtain a secondary ingot;
[0062] Step six, the secondary ingot obtained in step five is melted three times in a vacuum consumable arc furnace at a vacuum degree of less than 0.8Pa, a melting current of 25kA-30kA in the normal melting stage, a melting voltage of 37V-42V, an arc stabilizing current of 16A, and a switching time of the arc stabilizing current of 30s to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05%-0.20%.
[0063] Figure 4 is a physical picture of the interstitial carbon element alloyed high temperature titanium alloy ingot prepared in this embodiment, Figure 4 It can be seen that the prepared interstitial carbon element alloyed high-temperature titanium alloy ingot has a larger volume, no surface interlayer, obvious cold shut, scarring, smaller ingot head flash, and the ingot body is bright and free of oxidation.
[0064] The interstitial carbon element alloyed high temperature titanium alloy ingot prepared in this example was sampled at different positions. Figure 5 ,from Figure 5 It can be seen that samples are taken at various positions in the middle of the ingot body of the interstitial carbon element alloyed high-temperature titanium alloy ingot, and the sampling positions are numbered. Then the sampling results are tested for composition. The results are shown in Figure 6 ,from Figure 6 It can be seen that the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this embodiment has a uniform overall composition, no obvious composition fluctuation, and is consistent with the batching value.
[0065] The interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this example was sampled at the top, middle and bottom, and the composition was tested. The results are shown in Table 2.
[0066] Table 2
[0067] element Upper part (wt.%) Middle (wt.%) Lower part (wt.%) Al 7.01 6.98 6.99 Mo 1.51 1.52 1.50 Nb 1.01 0.99 0.97 Si 0.98 0.98 0.98 Sn 2.49 2.48 2.48 Ta 2.00 1.99 1.99 Zr 2.49 2.48 2.50 C 0.20 0.19 0.20
[0068] It can be seen from Table 2 that the composition differences of the interstitial carbon element alloyed high-temperature titanium alloy ingots prepared in this embodiment are all controlled within 0.15%.
[0069] Example 3
[0070] This embodiment is to prepare a high-temperature titanium alloy ingot alloyed with interstitial carbon elements having a composition of Ti-7Al-2.5Sn-2.5Zr-1.5Mo-2.0Ta-1.0Nb-1.0Si-0.05C.
[0071] This embodiment includes the following steps:
[0072] Step 1, titanium sponge particles with a particle size of 2mm to 3mm, 3N flake graphite powder with a particle size of 20 mesh to 40 mesh, and titanium oxide powder with a particle size of 300 mesh to 400 mesh are mixed for more than 3 minutes, and then aluminum-molybdenum alloy powder, niobium-titanium-aluminum alloy powder, aluminum-silicon alloy powder, titanium-tin alloy powder and aluminum-tantalum alloy powder with a particle size of 1mm to 6mm are added for secondary mixing for more than 3 minutes to obtain a mixture; the titanium sponge particles with a particle size of 2mm to 3mm meet the 0 grade titanium sponge or 0 in GB / T 2524-2019 standard A Requirements for grade titanium sponge;
[0073] Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in the pressing mold in a layered wrapped cloth form from bottom to top, and the mass of the titanium sponge particles of 0.83 mm to 12.7 mm in the upper and lower layers is equal, and then press, and repeat the above process to obtain a plurality of electrode blocks; the titanium sponge particles with a particle size of 0.83 mm to 12.7 mm meet the GB / T 2524-2019 standard 0 grade titanium sponge or 0 A Requirements for grade titanium sponge;
[0074] Step 3: welding the multiple electrode blocks obtained in step 2 by using a vacuum plasma welding gun to obtain a consumable electrode;
[0075] Step 4: The consumable electrode obtained in step 3 is melted once in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a melting current of 17kA-20kA in a normal melting stage, a melting voltage of 30V-35V, an arc stabilizing current of 20A, and a switching time of the arc stabilizing current of 30s to obtain an ingot;
[0076] Step 5, the primary ingot obtained in step 4 is subjected to secondary smelting in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a smelting current of 20kA-25kA in a normal smelting stage, a smelting voltage of 35V-37V, an arc stabilizing current of 18A, and a switching time of the arc stabilizing current of 30s to obtain a secondary ingot;
[0077] Step six, the secondary ingot obtained in step five is melted three times in a vacuum consumable arc furnace at a vacuum degree of less than 0.8Pa, a melting current of 25kA-30kA in the normal melting stage, a melting voltage of 37V-42V, an arc stabilizing current of 16A, and a switching time of the arc stabilizing current of 30s to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05%-0.20%.
[0078] After testing, the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this embodiment has a large volume, no surface interlayer, obvious cold shut, scarring, small ingot head flash, and the ingot body is bright and unoxidized. The overall composition is uniform, without obvious composition fluctuations, and is consistent with the ingredient value. The composition difference is controlled within 0.13%.
[0079] Example 4
[0080] This embodiment is to prepare a high-temperature titanium alloy ingot alloyed with interstitial carbon elements having a composition of Ti-7Al-2.5Sn-2.5Zr-1.5Mo-2.0Ta-1.0Nb-1.0Si-0.15C.
[0081] This embodiment includes the following steps:
[0082] Step 1, titanium sponge particles with a particle size of 2mm to 3mm, 3N flake graphite powder with a particle size of 20 mesh to 40 mesh, and titanium oxide powder with a particle size of 300 mesh to 400 mesh are mixed for more than 3 minutes, and then aluminum-molybdenum alloy powder, niobium-titanium-aluminum alloy powder, aluminum-silicon alloy powder, titanium-tin alloy powder and aluminum-tantalum alloy powder with a particle size of 1mm to 6mm are added for secondary mixing for more than 3 minutes to obtain a mixture; the titanium sponge particles with a particle size of 2mm to 3mm meet the 0 grade titanium sponge or 0 in GB / T 2524-2019 standard A Requirements for grade titanium sponge;
[0083] Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in the pressing mold in a layered wrapped cloth form from bottom to top, and the mass of the titanium sponge particles of 0.83 mm to 12.7 mm in the upper and lower layers is equal, and then press, and repeat the above process to obtain a plurality of electrode blocks; the titanium sponge particles with a particle size of 0.83 mm to 12.7 mm meet the GB / T 2524-2019 standard 0 grade titanium sponge or 0 A Requirements for grade titanium sponge;
[0084] Step 3: welding the multiple electrode blocks obtained in step 2 by using a vacuum plasma welding gun to obtain a consumable electrode;
[0085] Step 4: The consumable electrode obtained in step 3 is melted once in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a melting current of 17kA-20kA in a normal melting stage, a melting voltage of 30V-35V, an arc stabilizing current of 20A, and a switching time of the arc stabilizing current of 30s to obtain an ingot;
[0086] Step 5, the primary ingot obtained in step 4 is subjected to secondary smelting in a vacuum consumable arc furnace at a vacuum degree of less than 0.8 Pa, a smelting current of 20kA-25kA in a normal smelting stage, a smelting voltage of 35V-37V, an arc stabilizing current of 18A, and a switching time of the arc stabilizing current of 30s to obtain a secondary ingot;
[0087] Step six, the secondary ingot obtained in step five is melted three times in a vacuum consumable arc furnace at a vacuum degree of less than 0.8Pa, a melting current of 25kA-30kA in the normal melting stage, a melting voltage of 37V-42V, an arc stabilizing current of 16A, and a switching time of the arc stabilizing current of 30s to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05%-0.20%.
[0088] After testing, the interstitial carbon element alloyed high-temperature titanium alloy ingot prepared in this embodiment has a large volume, no surface interlayer, obvious cold shut, scarring, small ingot head flash, and the ingot body is bright and unoxidized. The overall composition is uniform, without obvious composition fluctuations, and is consistent with the ingredient value. The composition difference is controlled within 0.12%.
[0089] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot, characterized in that: The method comprises the following steps: Step 1: Mix titanium sponge particles with a particle size of 2 mm to 3 mm, flake graphite powder and titanium oxide powder, and then add intermediate alloy powder for secondary mixing to obtain a mixture; Step 2: Place titanium sponge particles with a particle size of 0.83 mm to 12.7 mm, the mixture obtained in step 1, and titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in a pressing mold in a layered wrapped cloth form from bottom to top, and then press them, and repeat the above process to obtain multiple electrode blocks; Step 3: welding the multiple electrode blocks obtained in step 2 to obtain consumable electrodes; Step 4, melting the consumable electrode obtained in step 3 to obtain an ingot; Step 5, performing secondary smelting on the primary ingot obtained in step 4 to obtain a secondary ingot; Step 6: Smelt the secondary ingot obtained in step 5 three times to obtain an interstitial carbon element alloyed high-temperature titanium alloy ingot with a carbon content of 0.05% to 0.20%.
2. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The titanium sponge particles with a particle size of 2 mm to 3 mm in step 1 and the titanium sponge particles with a particle size of 0.83 mm to 12.7 mm in step 2 both meet the requirements of grade 0 titanium sponge or grade 0 in GB / T 2524-2019. A Requirements for grade titanium sponge.
3. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: In step 1, the particle size of the flake graphite powder is 20-40 mesh, and the mass purity is 3N grade, the particle size of the titanium oxide powder is 300-400 mesh, and the particle size of the intermediate alloy powder is 1 mm-6 mm.
4. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The master alloy described in step 1 includes aluminum-molybdenum alloy, niobium-titanium-aluminum alloy, aluminum-silicon alloy, titanium-tin alloy and aluminum-tantalum alloy.
5. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The time for the first mixing and the second mixing in step 1 is not less than 3 minutes.
6. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The layered wrapped cloth in step 2 is specifically in the form of a portion close to the pressing mold covered and filled with titanium sponge having a particle size of 0.83 mm to 12.7 mm, with a mixture in the middle, and the upper and lower layers of titanium sponge particles of 0.83 mm to 12.7 mm having equal mass.
7. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The assembly welding described in step 3 is performed using a vacuum plasma welding gun.
8. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The primary smelting in step 4 is vacuum consumable arc melting using a vacuum consumable arc furnace. The vacuum degree of the primary smelting is less than 0.8 Pa. The smelting current in the normal smelting stage is 17kA-20kA, the smelting voltage is 30V-35V, the arc stabilizing current is 20A, and the switching time of the arc stabilizing current is 30s.
9. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The secondary smelting in step five is vacuum consumable arc melting using a vacuum consumable arc furnace. The vacuum degree of the secondary smelting is less than 0.8 Pa. The smelting current in the normal smelting stage is 20kA-25kA, the smelting voltage is 35V-37V, the arc stabilization current is 18A, and the switching time of the arc stabilization current is 30s.
10. The method for smelting an interstitial carbon element alloyed high temperature titanium alloy ingot according to claim 1, characterized in that: The three smeltings in step six are vacuum consumable arc melting using a vacuum consumable arc furnace. The vacuum degree of the three smeltings is less than 0.8 Pa. The smelting current in the normal smelting stage is 25kA-30kA, the smelting voltage is 37V-42V, the arc stabilization current is 16A, and the switching time of the arc stabilization current is 30s.
Citation Information
Cited By
Al-Mo-C intermediate alloy, high-temperature titanium alloy with Al-Mo-C intermediate alloy as raw material, and preparation method and application of Al-Mo-C intermediate alloy
CN121518881A
Preparation method of carbon-niobium composite ultrahigh-strength titanium alloy pipe
CN122142125A